Identification and Analysis of Estrogen Receptor α Promoting Tamoxifen Resistance-Related lncRNAs - Wang, Wei; Li, Zhen; Gao, Shanjun; Zhang, Xiulei; Liu, Guangzhi (BioMed research international, 2020)
70-75% breast cancer patients are estrogen receptor alpha positive (ERα+), and the antiestrogen drug tamoxifen has been used for the past three decades. However, in 20-30% of these patients, tamoxifen therapy fails due to intrinsic or acquired resistance. A previous study has showed ERα signaling still exerts significant roles in the development of tamoxifen resistance and several lncRNAs have been demonstrated important roles in tamoxifen resistance. But ERα directly regulated and tamoxifen resistance related lncRNAs remain to be discovered. We reanalyze the published ERα chromatin immunoprecipitation-seq (ChIP-seq) and RNA-seq data of tamoxifen-sensitive (MCF-7/WT) and tamoxifen-resistant (MCF-7/TamR) breast cancer cells. We demonstrate that there are differential ERα recruitment events and the differentials may alert the expression profile in MCF-7/WT and MCF-7/TamR cells. Furthermore, we make an overlap of the ERα binding lncRNAs and differentially expressed lncRNAs and get 49 ERα positively regulated lncRNAs. Among these lncRNAs, the expression levels of AC117383.1, AC144450.1, RP11-15H20.6, and ATXN1-AS1 are negatively correlated with the survival probability of breast cancer patients and ELOVL2-AS1, PCOLCE-AS1, ITGA9-AS1, and FLNB-AS1 are positively correlated. These lncRNAs may be potential diagnosis or prognosis markers of tamoxifen resistance.